SISTEM INFORMASI KEGIATAN PROGRAM STUDI TEKNIK INFORMTAIKA UNIVERSITAS MATARAM - Anggi Fitriani; Ariyan Zubaidi; Andy Hidayat Jatmika (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2020)
As an educational institution, each university competes to build an information system to provide the best service for all university citizens. Communication between lecturers, and between students is one of the focuses of the attention of managers of educational institutions. In this writing, the application of information technology is carried out to make a publication of activity reports for lecturers or students who are in the informatics engineering study program. Features in this system can facilitate students or academics in exploring information that is useful for their studies, such as providing information about publication of reports on seminars, guest lectures, workshops, and lecturers' services that have been carried out both within the faculty and the university itself or outside the university, where information on this activity can provide inspiration for lecturers and students themselves. conclusion: With the black box testing that has been done can show that all functions run correctly as desired.